Developing a Magic Pocket Game to Introduce Religious and Moral Values to 5-6 Year Old Children - Bety Fatqur Rohmah; Leli Fertiliana Dea; Isnaini Nur Azizah; Jauharotun Nafisah (Journal of Childhood Development, 2023)
Games are essential activities for early childhood because they provide enjoyable learning experiences. This study aims to develop and test the effectiveness of the "Magic Pocket" game in fostering religious and moral values in 5–6-year-old children at RA Bustanul Ulum Jayasakti, Anak Tuha District, Central Lampung Regency. The research method used is Research Methodology. and Development (R&D) with the Borg model and Gall . Data collection techniques include observation, interviews, documentation, and questionnaires. The results of the study indicate that the magic pocket game media is suitable for use with an average validation score of 3.25 after revision. This media is considered practical, interesting, fun, and durable, although it still requires teacher guidance when used. In terms of effectiveness, this game has been proven to be able to improve children's religious and moral values, where after implementation there were no more children in the "not yet developed" category. Thus, the magic pocket game is effective in supporting the development of children's religious character